Few Aspects Regarding the Building of the Rule of Law - Magureanu, Alexandru Florin (Journal of Economic Development, Environment and People, 2014)
<span style="color: black; line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN">Delegating the sovereignty from the citizens to the Government is necessary, to a certain degree, in order to ensure the efficiency of the constitution and the separation of powers, as well as the process of lawmaking. However the complex structure that we now call a “state” and that already seems to have reached its limitations is often perceived as a cold, impersonal structure, in which citizens are becoming only an insignificant part, an interchangeable wheel in a grand design. Thus the decision tends to become more distant from the citizens, than it was in the Greek democracy for example. The new means of communication, especially the Internet, give the citizen the possibility to be closer to the decisions taken by the legislator. The building of a “virtual agora” in which citizens are asked to participate directly to their own governing seems an achievable dream. Main difficulties towards such an ambitious goal are no longer of a technological nature, but of transforming the traditional law making process, the somehow rigid essential characteristics that the rule of law must have, with the direct exercise of sovereignty, by the citizens, if not in all matters, at least at a local, administrative level.